PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS APLIKASI PADA BUMDES CEMERLANG DI DESA PLEREAN - Alfin Nurul Afifah; Anggun Kumala Putri; Rizky Amelia; Tafiyatul Wulandari; Muhammad Nisfar Ramdhani; Arisona Ahmad (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service activity aims to enhance the financial reporting skills of the management of BUMDes Cemerlang in Plerean Village in accordance with SAK EMKM standards. The issues faced include a lack of understanding of accounting principles and limited use of digital technology. Through an Excel-based application approach, the service team conducted a series of activities including socialization, training, and direct assistance. The application used was tailored to the needs of BUMDes to simplify transaction recording and financial report preparation. The results showed improved understanding and skills among the management in more effective, efficient, and accountable financial management. Final evaluations indicated that the management found the application helpful in minimizing errors and accelerating the financial reporting process.